Molecular dynamic simulation of CO2 absorption into mixed aqueous solutions MDEA/PZ (Chemical Engineering Research Bulletin, 2017)
The mixture of amine absorption process is an approach for mitigation of carbon dioxide (CO2) from flue gas that produces from power plant. Several experimental and simulation studies have been undertaken to understand this process but the mechanism of CO2 absorption into the aqueous blended amines such as MDEA/PZ is not well understood and available knowledge within the open literature is limited. The aim of this study is to investigate the intermolecular interaction of the blended MDEA/PZ using Molecular Dynamics (MD) simulation. MD simulation was run under condition 313 K and 1 atm. The thermodynamic ensemble used were 200 ps for NVE and 1 ns for NVT. The periodic boundary is used to visualize the interaction of molecules of the whole system. The simulation method also involved calculation of force field and time integration algorithm.The results were interpreted in terms of Radial Distribution Function (RDF) analysis. It was observed that the hydroxyl group (OH) of MDEA is more attracted to water molecule compared to amino group (NH) of MDEA. The intermolecular interaction probability of OH and NH group of MDEA with CO2 in blended MDEA/PZ is higher than using pure MDEA. This finding shows that PZ molecule act as an activator to promote the intermolecular interaction between MDEA and CO2.Thus, blend of MDEA with PZ is expecting to increase the absorption rate of CO2 and reduce the heat regeneration requirement.Chemical Engineering Research Bulletin 19(2017) 1-11